1973
DOI: 10.1210/endo-92-4-1223
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations in Plasma Testosterone Levels in Adult Male Rats and Mice

Abstract: Testosterone (T) levels in the plasma of male laboratory rats and mice were measured by radioimmunoassay. There was a striking individual variation with values ranging from less than 1 ng/ml to over 30 ng/ml in mice of the same age and strain housed under identical conditions. Using chronic indwelling catheters inserted into a jugular vein, blood was collected from adult conscious male rats every 24 hr for 4 or 8 days and every 30 min for 2 l / 2 or 8 hr. Considerable differences in plasma T levels were observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
108
3

Year Published

1975
1975
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(128 citation statements)
references
References 31 publications
17
108
3
Order By: Relevance
“…Testosterone levels in the present experiment are higher than those reported for individually housed rats (0.2 -1.5 ~g%, mean = 0.6t~g%) by Bartke et al [3], but within the same range as those reported by the same authors for mice housed 4/cage (0.04 -4.4 ~g%, mean = 1.9~g%). To our knowledge, testosterone levels for gerbils have not been reported.…”
Section: Discussionsupporting
confidence: 62%
“…Testosterone levels in the present experiment are higher than those reported for individually housed rats (0.2 -1.5 ~g%, mean = 0.6t~g%) by Bartke et al [3], but within the same range as those reported by the same authors for mice housed 4/cage (0.04 -4.4 ~g%, mean = 1.9~g%). To our knowledge, testosterone levels for gerbils have not been reported.…”
Section: Discussionsupporting
confidence: 62%
“…The within assay co- given study were run in the same assay. Plasma T, DHT, and E were also determined by radioimmunoassay after column chromatography (15,16). The between assay coefficient of variation of these assays is less than 20% and within assay coefficient of variation is less than 10%, respectively.…”
Section: Hormone Assaysmentioning
confidence: 99%
“…A large number of studies sin rodents and primates suggest that spontaneous LU pulses reflect the periodic secretion of LU-RU from the hypothalamus in response to firing of a-adrenergically mediated CNS neurons (14,(28)(29)(30)(31). If this consideration 15 correct, LU pulse amplitude could be modulated either by (a) the amount of endogenous LU-RU released to initiate each spontaneous LU pulse or (b) by the responsiveness of the pituitary to a given quantity of LU-RU. Administration of exogenous LU-RU allowed distinction between these two possibilities.…”
Section: Pulsatile Lh Releasementioning
confidence: 99%
“…The individual testosterone (T) levels vary markedly, which has been previously observed in mice (Bartke et al, 1973;Bartke and Dalterio, 1975;Klomberg et al, 2002). Plasma T levels were ranged from 0.24 to 37.7 ng/ml (n=76), and from 0.19 to 60.1 ng/ml (n=73) in adult male mice (Klomberg et al, 2002).…”
Section: Introductionmentioning
confidence: 68%